Bark thickness does not explain the different susceptibility of Australian and New Zealand temperate rain forests to anthropogenic fire. (19th February 2014) - Lawes, Michael J.; Richardson, Sarah J.; Clarke, Peter J.; Midgley, Jeremy J.; McGlone, Matt S.; Bellingham, Peter J.; Higgins, Steven
Abstract Aim Anthropogenic fires caused New Zealand's temperate rain forests to decline rapidly from 80% to 50% cover after Polynesian arrival. In contrast, Australian temperate rain forests have remained stable in spite of a longer history of fire and human occupation. We evaluate whether New Zealand's conifer‐dominated forests declined because they lack fire resistance traits. We predicted that New Zealand species should have thinner bark than their Australian counterparts, and slower growing conifers should have relatively thicker bark than angiosperms. Location Temperate rain forests of south‐eastern Australia, Tasmania and New Zealand. Methods We examined the ratio of bark thickness to stem diameter (relative bark thickness) as a standardized index (by tree size) of fire resistance. Nonlinear power models were fitted to examine trends in relative bark thickness between trees from New Zealand and Australia. Bark thickness was also compared between species pairs and congeners and by phylogenetically corrected ANOVA. Results Although angiosperms and gymnosperms in New Zealand had thin bark in a global context, they had significantly thicker bark than their Australian counterparts. Bark thickened more rapidly for small trees in New Zealand but declined with increasing stem diameter. Allocation to bark thickness was greater for larger stems in Australia. New Zealand gymnosperms had the thickest bark of all species examined. Main conclusions Fire resistance is a complex syndrome comprising functional traits that ensure protection (resistance – bark) from and recovery (resilience – resprouting) after fire. Thin bark in temperate rain forests suggests weak selection by fire on bark traits. However, the stability of Australian temperate forests in a flammable landscape emphasizes the importance of resprouting, especially basal resprouting, to forest persistence after fire. New Zealand forests do not resprout after fire and lack the fire resistance traits required for recovery from repeated anthropogenic fires.